2020
DOI: 10.1097/bpo.0000000000001590
|View full text |Cite
|
Sign up to set email alerts
|

Thoracoscopic Vertebral Body Tethering for Adolescent Idiopathic Scoliosis: A Minimum of 2 Years’ Results of 21 Patients

Abstract: Background: Anterior vertebral body tethering (VBT) is a growth modulating and fusionless treatment option that is considered as a new promising method for the management of adolescent idiopathic scoliosis (AIS). This prospective cohort study aimed to present the minimum 2-year results of anterior VBT applied to 21 skeletally immature patients with AIS. Methods: Twenty-one skeletally immature patients with a diagnosis of AIS were included. A decision to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 27 publications
1
40
0
2
Order By: Relevance
“…This surgical technique has been shown to have an acceptably low perioperative complication pro le and a relatively short learning curve even for surgeons not previously familiar with anterior spinal surgery [11,25,26]. Although promising results are increasingly being reported, little is as yet known about the ideal candidate, the optimal surgical planning and the best surgical technique [8,25,27,28]. In our own clinical experience, we noticed that skeletal maturity and curve exibility may not be the most important parameters for our decision making, as good results have been obtained both in growing patients and in patients approaching skeletal maturity [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…This surgical technique has been shown to have an acceptably low perioperative complication pro le and a relatively short learning curve even for surgeons not previously familiar with anterior spinal surgery [11,25,26]. Although promising results are increasingly being reported, little is as yet known about the ideal candidate, the optimal surgical planning and the best surgical technique [8,25,27,28]. In our own clinical experience, we noticed that skeletal maturity and curve exibility may not be the most important parameters for our decision making, as good results have been obtained both in growing patients and in patients approaching skeletal maturity [1,20].…”
Section: Discussionmentioning
confidence: 99%
“…57 At this WTP threshold, VBT was cost-effective in 66.4% of probabilistic iterations, suggesting that the results are robust with respect to combined parameter uncertainty, although the limitations associated with studies reporting clinical outcomes for the VBT procedure should be considered in the interpretation of these findings. At the time of these analyses, studies reporting clinical outcomes for the VBT procedure include relatively small patient numbers, [34][35][36][37][38] with a small subset of those who reported key patient-reported outcomes 34,35 needed for a costeffectiveness analysis as compared to the extensive reporting of studies describing spinal fusion for pediatric patients with IS spanning decades and large sample sizes. 7,43 Also, studies reporting clinical outcomes for the VBT procedure provide a maximum length of follow-up of 7 years, whereas the base case time horizon for the CUA was 15 years.…”
Section: Discussionmentioning
confidence: 99%
“…Anterior vertebral body tethering (VBT) is a nonfusion, minimally invasive growth-modulating procedure that can provide treatment without the need for fusion ( Figure 1B); early reports of the clinical efficacy and safety of VBT indicate some positive outcomes for skeletally immature patients aged >10 years with IS. [34][35][36][37][38] Spinal tethering offers an alternative treatment to spinal fusion for pediatric patients aged >10 years with IS where significant continued growth is expected. Compared with spinal fusion, VBT may minimize the impact on growth while offering improved range of motion and faster return to normal activities.…”
mentioning
confidence: 99%
“…The latter authors evaluated preliminary 1-year outcomes of VBT patients and demonstrated a mean 24.9° correction of thoracic curves, with only 1 reported medical complication (atelectasis). Like other previous studies, their emphasis was on Lenke 1 (main thoracic) curves [6,8,[11][12][13]15], whereas Hoernschemeyer et al evaluated efficacy across subgroups on the basis of curve type and treatment, maintained a high follow-up rate (93.5%), and had well-defined time points to assess radiographic outcomes postoperatively and at 6 months, 1 and 2 years, and most recent follow-up.…”
Section: Commentarymentioning
confidence: 99%
“…Given its novelty, the optimal indications and long-term outcomes for VBT have yet to be elucidated. Several studies have shown successful VBT treatment with intervention limited to patients with main thoracic curves [6,11,13,15]. Without long-term outcomes, it is difficult to compare VBT to other methods of spinal deformity correction.…”
Section: Introductionmentioning
confidence: 99%